PEMBERDAYAAN WARGA DAN KELOMPOK TANI CANDEN DALAM MENGEMBANGKAN PANEL SURYA SEDERHANA DARI BARANG BEKAS DVD: EMPOWERMENT OF CITIZENS AND CANDEN FARMING GROUP IN DEVELOPING SIMPLE SOLAR PANEL FROM USED DVD GOODS - Westri Andini, Dinar; Saputro, Handoyo; Setya Ratri, Wahyu; Sudigdo, Anang (Universitas PGRI Yogyakarta, 2023)
Supporting development and making the community have advanced and modern thinking, it is necessary to empower them so that they are empowered, independent, and able to solve the problems they face. Likewise what happened in Canden Village, that there are still areas where it is difficult to get irrigation. Through activities that provide stimulus activities that aim through modeling and direct discussion in heterogeneous groups, they are able to generate participation and brilliant ideas to be able to solve the watering problems they are experiencing through the use of used DVDs as solar panels. Community members consisting of young people and farmer groups were able to participate actively and produce a simple solar panel prototype from 6 DVDs arranged in parallel Key words: reuse, DVD, participation, empowerment, agriculture